Tari Dan Pendidikan - Soemaryatmi Soemaryatmi (Institut Seni Indonesia Surakarta, 2011)
In Indonesia, dancing education get less attention or called has lower quality than others. This is the reason why dancing education included into local curricula and considered as a subject matter which is not useful to evaluate the progress of learners. The aim of dancing education is not to study gesture only, but also mental attitude, discipline, self-confidence, the attitude to accept, appraise and cooperate with other person. Through dancing education, learners do not receive art knowledge based on social and cultural value only; however, they have opportunities to do creative activities by trainings. Creative activities are manifestation of their communication skill with other people and their environment and self-actualization in their live. About those manners, teacher as the mainstay expected bring her/his role as mediator to improve societies art appreciation. It means that role of art teacher, especially dancing, not only arranges Learning Application Plan (Rencana Pelaksanaan Pembelajaran) but also gives information by printed or electronic medium, produces work of art and presents some performances within her/his society. The key and effort to improve aesthetical ability of children is how the government appreciates work of art and brings it into its policies proportionally. Keywords: dance, curricula, role of teacher, and approach.